Rumah Lontiok sebagai Simbol Kehidupan Masyarakat Kampar - Adinda Aristawidia Sahda; Elmustian Rahman; Nurhidayati Nurhidayati; Reva Aulia Putri; Widya Eliza; Jihan Nabila; Nadia Arsalina; Purnama Sari (Journal of Creative Student Research, 2024)
Rumah Lontiokis a traditional house of the Kampar community that symbolizes cultural identity and philosophical values. Built for the first time in 1889 and utilized starting in 1900, this house is unique due to the absence of rooms, the presence of five symbolic levels, and water facilities for purification. This research aims to identify the cultural values embedded in Rumah Lontiok and promote its preservation. The method employed is descriptive qualitative, with direct observation conducted in Kampung Pulau Belimbing, Riau. The findings reveal that Rumah Lontiok holds high cultural significance, particularly regarding the philosophy of togetherness, harmony with nature, and spirituality. This traditional house is also supported by two legal foundations: customary values and local beliefs. However, modernization poses a threat to its existence, necessitating cultural revitalization to ensure Rumah Lontiok's preservation.